PERAN THE NATURE CONSERVANCY (TNC) DALAM PELAKSANAAN KONSERVASI TAMAN NASIONAL PERAIRAN LAUT SAWU - Radha Novia Sandi; Irwan Iskandar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Savu Sea Marine National Park is an important habitat and migratory corridor for cetaceans and turtles, a key nursery area for fish, and refuge for coral reefs. However, resources are being threatened by unsustainable and destructive fishing pressure and increasing coastal development. In response to these threats, the Indonesian Ministry of Marine Affairs and Fisheries made a decision to invited TNC participate in implementing conservation at Savu Sea Marine National Park. TNC is an international organization dedicated to the mission of conserving biodiversity throughout the world. This research used qualitative descriptive analysis method of primary and secondary data collection techniques. These data obtained from interview, official website, official document, journal and other literature. The author uses pluralism perspective with group analysis level, international organization theory and international politics of environment concept. The result of this research is TNC has active roles in implementing conservation at Savu Sea Marine National Park. The author classified TNC’s role in two categories, as an initiator by initiating program to resolve the problems and a facilitators by facilitating conservation activities at Savu Sea Marine National Park.. Keywords: Conservation, Facilitator, Iniatiator, Marine National Park, Role, Savu Sea, International Organization.